Women's Political Communication in Africa
XIII, 172 p. 6 illus., 3 illus. in color.
Keywords: This book examines women’s political communication in Africa, capturing previously unheard women’s voices, and presenting detailed information on overlooked communication strategies and forms of power relations employed by African women and women of African descent. By examining the disputes, accomplishments and/or setbacks experienced by women in political spaces, it underscores feminist intersections of political communication in Africa. It also explores the glamor, humor, harmony and tact that women as state and non-state actors have contributed to Africa’s political landscape through the realities of female soft power. The book addresses issues concerning how and why women do and should participate in politics; at what level they have employed political communication strategies; and which types. It also questions ideas and ideals that have guided or continue to guide feminist politicalcommunication in Africa’s growing democracy. Lastly, it highlights African women’s conscious approach and rejuvenated interest in developing their communication skills and strategies given their vital role in state-building.